Building the perfect team team role types - Garden, Graeme; Video Arts Production (London : Video Arts, 1990)
People bring more than their skills and experience to a team ; they bring their personality as well. Utilising people's behavioural strengths to create a balanced team can add immensely to both group and personal performance
Copy available in DVD format
Keywords: Work groups